P‐ and E‐ selectin in venous thrombosis and non‐venous pathologies. (25th March 2022) - Purdy, Megan; Obi, Andrea; Myers, Daniel; Wakefield, Thomas
Abstract: Venous thromboembolism is a very common and costly health problem worldwide. Anticoagulant treatment for VTE is imperfect: all have the potential for significant bleeding, and none prevent the development of post thrombotic syndrome after deep vein thrombosis or chronic thromboembolic pulmonary hypertension after pulmonary embolism. For these reasons, alternate forms of therapy with improved efficacy and decreased bleeding are needed. Selectins are a family (P‐selectin, E‐selectin, L‐selectin) of glycoproteins that facilitate and augment thrombosis, modulating neutrophil, monocyte, and platelet activity. P‐ and E‐selectin have been investigated as potential biomarkers for thrombosis. Inhibition of P‐selectin and E‐selectin decrease thrombosis and vein wall fibrosis, with no increase in bleeding. Selectin inhibition is a promising avenue of future study as either a stand‐alone treatment for VTE or as an adjunct to standard anticoagulation therapies.